IMPROVING THE STUDENT'S OPINION ABOUT THE NATURE OF SCIENCE WITH THE PROCESS-BASED ACTIVITIES BY THE TEACHERS WHO GET DISTANCE EDUCATION ABOUT THE NATURE OF SCIENCE - Fatih Serdar Yıldırım; Semra Mirici (Informascope, 2016)
The purpose of this research is to identify the effect of the activities on student's opinion about the science nature which is prepared with the explicit reflective teaching approach and integrated with 9th grade biology lesson syllabus by the teachers who gets distance education about teaching the nature of science. For that purpose, in this research, quasi experimental design with pretest and posttest control group has been used. For that purpose, in this research, quasi experimental design with pretest and posttest control group has been used. 2 teachers and 114 students in an Anatolian High School in Meram/Konya have participated in this research in the whole 2014-2015 academic year. In this project, BDHGA Form C (a survey on the ideas about nature of the science), and YYG (semi-structured interview) and Rubic are used as data collecting tools. The qualitative data of the research has been analyzed with content analysis, descriptive analysis and document review. The quantitative data has been analyzed with the SPSS 17 software using ANOVA and T-test for related samples. According to the both quantitative and qualitative data obtained from the research, the experiment class, in which the teacher educated in distant about nature of science and has taught the topic in process based way to the students, is observed to be more developed in this topic than the other class. Also it is seen that only being educated about science nature of the teachers is not adequate. However, the usage of the explicit reflective activities integrated into syllabus has contributed to the perception of the students about the nature of science topic.